THE EFFECT OF TENSES PERIODIC TABLE ON ELEVENTH GRADERS’ SIMPLE PRESENT AND FUTURE TENSES AT SMK NEGERI 4 TARAKAN - Abiyyu, Raihan Langgeng; Eppendi, Jhoni; Agus, Rianto (Universitas Borneo Tarakan, 2023)
The study examined whether there was a significant difference between pupils taught using the tenses periodic table and those who were not. The pre-experimental design of the study included one group pre-testing and post-testing. Eleventh-grade Multimedia 2 students comprised the study's sample population. The paired sample t-test was utilized to investigate the data during analysis. The values for normality and homogeneity were 0.216 (0.05) for normality and 0.383 (0.05) for homogeneity. The study showed a 99% improvement between the pre-test and post-test results, with the pre-test mean score being 32.97 and the post-test mean score being 65.78. The results indicated that Ha is accepted and Ho is rejected. It indicates that the tenses periodic table is suitable for assisting eleventh-grade students of SMKN 4 Tarakan to enhance their ability to use straightforward present and future tenses.